Enhancement of As(v) adsorption from aqueous solution by a magnetic chitosan/biochar composite. Issue 18 (10th February 2017) - Liu, Shaobo; Huang, Binyan; Chai, Liyuan; Liu, Yunguo; Zeng, Guangming; Wang, Xin; Zeng, Wei; Shang, Meirong; Deng, Jiaqin; Zhou, Zan
Abstract : In this study, a magnetic chitosan/biochar composite (MCB) was prepared successfully, and characterized by SEM, TEM, VSM, XRD, FTIR, XPS, and zeta-potential to obtain its physical and chemical properties. Abstract : In this study, a magnetic chitosan/biochar composite (MCB) was prepared successfully, and characterized by SEM, TEM, VSM, XRD, FTIR, XPS, and zeta-potential to obtain its physical and chemical properties. The influence of different sorption parameters such as pH, contact time, initial As(v ) concentration, and temperature on As(v ) removal were studied thoroughly in order to optimize the reaction conditions. The results showed that the MCB adsorbed more As(v ) (11.961 mg g −1 ) than pristine biochar (3.681 mg g −1 ). In addition, the adsorption behavior could be well described by a pseudo-second-order and Langmuir model. Thermodynamic parameters revealed that the sorption reaction was a spontaneous and endothermic process. The adsorbed MCB could be effectively regenerated by 1.0 mol L −1 NaOH, and the adsorption capacity decreased from 11.823 to 8.078 mg g −1 in five cycles. In conclusion, MCB could be used as an efficient adsorbent for environment purification and conveniently separated from aqueous solution after adsorption.